THE PROS AND CONS OF ONLINE EDUCATION: THE PROS AND CONS OF ONLINE EDUCATION - Boltayeva, Dilfuzaxon (Журнал иностранных языков и лингвистики, 2021)
Today, many individuals are studying online: taking courses, learning new programs, and even changing their profession. Technologies are developing at a rapid rate, so it makes no sense to ignore the opportunities for rapid development. In addition, these are times of fierce competition, and entrepreneurs are forced to master new tools and technologies in order to stay ahead of their competitors. For this reason, distance learning, which will be discussed in this article, is rapidly developing. We will not talk about the pros and cons of distance education for students but will consider the advantages and disadvantages of online courses for entrepreneurs.